Biases in fiscal multiplier estimates - Zareh Asatryan; Annika Havlik; Friedrich Heinemann; Justus Nover (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
The "true" size of fiscal multipliers is widely debated by economists and policy makers as large (small) multipliers provide arguments to expand (cut) public spending. Within a meta-analytical framework, we ask whether the large observed variance in multiplier estimates can be explained by the national imprint and various author incentives. For this purpose, we use data on economists' personal characteristics including results from a selfconducted author survey. Our evidence is consistent with the hypotheses that the national background of researchers and the interests of donors financing the research matter for the degree and direction of multiplier estimates. These potential biases largely disappear for teams of international co-authors.
Keywords: B4; D72; E62; H11; 330; biased research; fiscal multipliers; funding bias; publication bias